PP.10.05: PREVALENCE OF TARGET ORGAN DAMAGE IN THE ELDERLY IN A GENERAL POPULATION IN NORTHERN ITALY. (June 2015) - Salvetti, M.; Paini, A.; Rosei, C. Agabiti; Bertacchini, F.; Maruelli, G.; Colonetti, E.; Donini, C.; Germano, R.; Casella, E.; Rosei, E. Agabiti; Muiesan, M.L.
Abstract : Objective: Current hypertension guidelines recommend evaluation of preclinical organ damage (OD) for cardiovascular risk assessment. Previous studies have indicated that in elderly subjects the prevalence of OD is high, but few data are available on the prevalence of various forms of OD in elderly subjects (E) as compared to non-elderly (NE) in a general population. Design and method: A total of 478 subjects (mean age 58 ± 10, range 43–74 yrs), 44%males, 69% hypertensives (37% treated), 17% obese, underwent clinical examination with blood pressure (BP) measurement (clinic and 24 hours), standard laboratory examinations, echocardiography, measurement of carotid femoral pulse wave velocity (PWV) and carotid intima media thickness (IMT). OD was defined, according to ESH ESC 2013 Guidelines. Results: 40% of patients were classified as E (> 64 years). SBP values were greater in E (clinic: 148 ± 15 vs 133 ± 13 mmHg, 24 h: 125 ± 13 vs 119 ± 11 mmHg, all p < 0.01). The prevalence of hypertension was greater in E as compared to NE (86% vs 53%, chi square p < 0.001). The prevalence of LVH was 31% in E as compared to 8.1 % in NE (Chi square p < 0.001). Also vascular damage was significantly more frequent in E: increased PWV was observed in 69% of E and in 21% of NE (chi square p < 0.001) and carotid structural damage (increased IMT or presence of a plaque) was observed in 96% of E and 64 % of NE (chi square p < 0.001). The overall prevalence of OD was greater in E (98.4 vs 67.7%, chi square p < 0.001); The simultaneous presence of 2 forms of OD was observed in 59 % of E and in 17 % of NE and the simultaneous presence of 3 forms of OD was observed in 14 % of E and in 3 % of NE. Conclusions: In a general population the prevalence of OD is particularly high in elderly patients as compared to middle age subjects. The coexistence of more than one form of OD is common in elderly patients and might contribute to the increased CV risk in these subjects.